Evaluating of economic indicators of the quality of living in the city of Al-Faw - Thabet Khalaf Al-Tayeb , Researcher. Sabreen; Ismail Othman, Assist. Prof. Dr. Osama (Basra studies journal, 2023)
The study aimed at measuring the analysis and evaluation of the quality of economic life in the city of Al-Faw according to economic indicators, like (the percentage of the population of working age, the unemployment rate, the actual dependency, the percentage of income, savings, and the population that owns private cars). It also work on knowing the levels of quality of life, and their spatial variance at the level of The neighborhoods through objective and subjective indicators and whether they are sufficient to satisfy the needs of population in the city of Faw. As well as the study is analyzing and explaining the reasons behind the varying levels of quality of life in the neighborhood cities of Al Faw district.